Predictable real-time constraints reveal anticipatory strategies of coupled planning in a sequential pick and place task. Issue 4 (April 2020) - Lewkowicz, Daniel; Delevoye-Turrell, Yvonne N
Planning a sequence of two motor elements is much more than concatenating two independent movements. However, very little is known about the cognitive strategies that are used to perform fluent sequences for intentional object manipulation. In this series of studies, the participants' task was to reach for and pick to place a wooden cylinder to set it on a place pad of three different diameters, which served to modify terminal accuracy constraints. Participants were required to perform the sequences (1) at their preferred speed or (2) as fast as possible. Action kinematics were recorded with the Qualisys motion-capture system in order to implement a real-time protocol to get participants to engage in a true interactive relation. Results revealed that with low internal constraints (at preferred speed), low coupling between the two elements of the motor sequence was observed, suggesting a step-by-step planning strategy. Under high constraints (at fastest speed), an important terminal accuracy effect back propagated to modify early kinematic parameters of the first element, suggesting strong coupling of the parameters in an encapsulated planning strategy. In Studies 2 and 3, we further manipulated instructions and timing constraints to confirm the importance of time and predictability of external information for coupled planning. These findings overall sustain the hypothesis that coupled planning can take place in a pick and place task when anticipatory strategies are possible. This mode of action planning may be the key reason why motor intention can be read through the observation of micro variations in body kinematics.